How Data and AI Can Optimise Pharmaceutical Supply Chains - Kumar*, Arun HS (Biology, Engineering, Medicine and Science Reports, 2026)
Pharmaceutical supply chains are highly complex, global, and tightly regulated systems that are increasingly exposed to disruption from geopolitical instability, pandemics, and demand volatility. This report examines how data and Artificial Intelligence (AI) can optimise pharmaceutical supply chains by improving forecasting accuracy, manufacturing efficiency, inventory management, logistics, quality assurance, and regulatory compliance. It argues that the industry is transitioning from isolated AI pilots toward integrated, intelligent, and potentially autonomous supply chain systems underpinned by data-driven decision-making, digital twins, and agentic AI. The report highlights the foundational role of data, emphasising that its value depends on contextualisation, integration, and governance across fragmented systems. AI applications such as machine learning-based demand forecasting, predictive inventory optimisation, and real-time analytics enable more responsive and efficient supply chain operations. In manufacturing, digital twins and predictive maintenance systems improve yield, reduce downtime, and enhance quality consistency, while AI-enabled logistics and warehouse optimisation strengthen cold-chain integrity and distribution efficiency. The report also explores AI applications in quality management and regulatory compliance, including anomaly detection, computer vision inspection, and automated documentation aligned with Good Manufacturing Practice (GMP) standards. Major technology providers such as IBM, SAP, Siemens, Microsoft, and GE Digital are enabling these capabilities through advanced industrial AI platforms. Finally, the report considers the emerging potential of agentic AI to enable autonomous decision-making across end-to-end supply chains, while recognising persistent challenges related to data quality, regulatory constraints, cybersecurity risks, and organisational readiness. Overall, the findings suggest that AI has the potential to transform pharmaceutical supply chains into more resilient, adaptive, and patient-centric systems, provided that technological innovation is matched with robust governance and organisational change.
Keywords: Agentic AI; Artificial Intelligence; Digital twins; Pharmaceutical Supply Chains; Predictive Analytics